Biomimetic materials based on hydroxyapatite patterns for studying extracellular cell communication - Polina I. Zyrianova; Mervat M. Eltantawy; Danil V. Silin; Ilya S. Korolev; Konstantin G. Nikolaev; Dmitry A. Kozodaev; Alla S. Slautina; Roman A. Surmenev; Andrei L. Kholkin; Sviatlana A. Ulasevich; Ekaterina V. Skorb (Materials & Design, 2024)
The study of cellular ion channels forms a basic understanding of healthy organ functioning and the body as a whole; however, the native role of signal transmission through ion channels between cells remains unclear. The success of the signal transmission investigation depends on the methods and materials used. Therefore, it is necessary to develop a new approach and system for studying detecting cell–cell communication. In this work, we suggest the system of hydroxyapatite patterns demonstrating piezoresponse in conjunction with fiber-based biosensors for detection of electrical signaling in cellular communities. Our system does not disrupt the integrity of cell membrane. The cells are located on self-assembled hydroxyapatite patterns forming the tissue patterns and communicating via spatially propagating waves of calcium, sodium, and potassium ions. These waves result from positive feedback caused by the activation of Ca2+ channels. The fiber-based ion-selective microelectrodes fixed above the patterns are used to detect the sodium, potassium, calcium ion currents in the extracellular space. We use norepinephrine to activate the Ca2+ channels result in intracellular Ca2+ release between the cell communities on different patterns. This system could be perspective as an efficient platform to lab-on-a-chip study as well as fundamental understanding of cellular communication during regeneration.